Plyometric exercise combined with high-intensity interval training improves metabolic abnormalities in young obese females more so than interval training alone - Racil, Ghazi; Zouhal, Hassane; Elmontassar, Wassim; Ben Abderrahmane, Abderraouf; De Sousa, Maysa Vieira; Chamari, Karim; Amri, Mohamed; Coquart, Jeremy B (Applied physiology, nutrition, and metabolism, 2016)
The aim of this study was to compare the effects of 12 weeks of high-intensity interval training (HIIT) with the effects of 12 weeks of plyometric exercise combined with HIIT (P+HIIT) on anthropometric, biochemical, and physical fitness data in young obese females. Sixty-eight participants (age, 16.6 ± 1.3 y; body mass, 82.8 ± 5.0 kg; body fat, 39.4% ± 3.3%; body mass index z score, 2.9 ± 0.4) were assigned to 1 of 3 groups: HIIT (2 blocks per session of 6-8 bouts of 30-s runs at 100% velocity at peak oxygen uptake, with 30-s active recovery between bouts at 50%velocity at peak oxygen uptake (n = 23)); P+HIIT (2 blocks per session of 3 different 15-s plyometric exercises with 15-s passive recoveries, totaling 2 min for each plyometric exercise + the same HIIT program (n = 26)); or control (no exercise (n = 19)). Anthropometric (body mass, body mass index z score, body fat, lean body mass, and waist circumference), biochemical (plasma glucose, insulin, leptin and adiponectin concentrations, leptin/adiponectin ratio, and homeostasis model assessment of insulin resistance (HOMA-IR)), physical fitness (peak oxygen uptake, velocity at peak oxygen uptake, squat jump, and countermovement jump performances), and energy intake data were collected. Both training programs improved the anthropometric, biochemical, and physical fitness variables. However, the P+HIIT program induced greater improvements than did the HIIT program in lean body mass (+3.0% ± 1.7%), plasma glucose and leptin concentrations (-11.0% ± 4.7% and -23.8% ± 5.8%, respectively), plasma leptin/adiponectin ratio (-40.9% ± 10.9%), HOMA-IR (-37.3% ± 6.2%), and squat jump performance (22.2% ± 7.5%). Taken together, these findings suggest that adding plyometric exercises to a HIIT program may be more beneficial than HIIT alone in obese female adolescents.